ANALISIS KECENDERUNGAN PEMILIHAN KOSMETIK WANITA DI KALANGAN MAHASISWI JURUSAN STATISTIKA UNIVERSITAS DIPONEGORO MENGGUNAKAN BIPLOT KOMPONEN UTAMA - Rizka Asri Brilliani; Diah Safitri; Sudarno Sudarno (Jurnal Gaussian, 2016)
This study aims to reviews trend of using the cosmetics brand among the students of Department of Statistics at Diponegoro University. The observed cosmetics brand are Wardah, Sariayu Martha Tilaar, Pixy, Pond's, and Garnier. The data used in the form of primary data with total samples drawn 180 students, then it's been analyzed using principal component biplot. The result showed that Wardah has advantages in safety of product composition, and its benefit as a skin care. Wardah also more attractive to students. Sariayu Martha Tilaar, Pixy, and Pond's have the same profit, they are safety of product composition, the variations according the skin type, and their use as a skin care and make up. The diversity is 73,01% which means that principal component analysis biplot is able to explained 73,01% of the total diversity of the actual data. Keywords: principal component biplot analysis, cosmetics brand, perceptions